3D Graphene Fibers Grown by Thermal Chemical Vapor Deposition. Issue 12 (9th February 2018) - Zeng, Jie; Ji, Xixi; Ma, Yihui; Zhang, Zhongxing; Wang, Shuguang; Ren, Zhonghua; Zhi, Chunyi; Yu, Jie
Abstract: 3D assembly of graphene sheets (GSs) is important for preserving the merits of the single‐atomic‐layered structure. Simultaneously, vertical growth of GSs has long been a challenge for thermal chemical vapor deposition (CVD). Here, vertical growth of the GSs is achieved in a thermal CVD reactor and a novel 3D graphene structure, 3D graphene fibers (3DGFs), is developed. The 3DGFs are prepared by carbonizing electrospun polyacrylonitrile fibers in NH3 and subsequently in situ growing the radially oriented GSs using thermal CVD. The GSs on the 3DGFs are densely arranged and interconnected with the edges fully exposed on the surface, resulting in high performances in multiple aspects such as electrical conductivity (3.4 × 10 4 –1.2 × 10 5 S m −1 ), electromagnetic shielding (60 932 dB cm 2 g −1 ), and superhydrophobicity and superoleophilicity, which are far superior to the existing 3D graphene materials. With the extraordinary properties along with the easy scalability of the simple thermal CVD, the novel 3DGFs are highly promising for many applications such as high‐strength and conducting composites, flexible conductors, electromagnetic shielding, energy storage, catalysis, and separation and purification. Furthermore, this strategy can be widely used to grow the vertical GSs on many other substrates by thermal CVD. Abstract : 3D graphene fibers (3DGFs) are successfully synthesized by vertically growing graphene sheets on polymer‐derived carbon nanofibers carbonized in NH3 using thermal chemical vapor deposition. The 3DGFs exhibit high electrical conductivity (3.4 × 10 4 –1.2 × 10 5 S m −1 ), electromagnetic shielding effectiveness (60 932 dB cm 2 g −1 ), and superhydrophobicity and superoleophilicity, far superior to the existing 3D graphene materials.